The Effect of Intrauterine Administration of Human Chorionic Gonadotropin (hCG) Before Embryo Transfer During Assisted Reproductive Cycles: a Meta-Analysis of Randomized Controlled Trials - Tan, Huiping; Hu, Shifu; Qiongyu; Chen, Yuan; Jin, Lei; Wu, Chunlin (Geburtshilfe und Frauenheilkunde, 2019)
The fertility success rates of clinical and laboratory-assisted reproductive techniques (ART) remain low, despite major advances. The aim of this study was to conduct a systematic literature review and assess whether the intrauterine administration of human chorionic gonadotropin (hCG) before embryo transfer (ET) improved the clinical outcomes of sub-fertile women undergoing assisted reproduction. The electronic databases PUBMED, EMBASE and Web of Science were systematically searched for randomized controlled trials (RCTs) published from inception to June 2018. The trial data were independently extracted and analyzed using risk ratios (RRs) and 95% confidence intervals (CIs) according to a random- or fixed-effect model (as appropriate), and a meta-analysis was conducted using Review Manager 5.2 software. The meta-analysis included 3241 patients from 12 RCTs, and the combined results demonstrated that intrauterine hCG injection significantly improved the rates of clinical (RR = 1.33; 95% CI: 1.12 – 1.58) and ongoing pregnancy (RR = 1.87; 95% CI: 1.54 – 2.27), compared with controls. However, intrauterine hCG injection had no significant effect on the implantation rate (RR = 1.30; 95% CI: 0.89 – 1.90), abortion rate (RR = 1.06; 95% CI: 0.78 – 1.44), ectopic pregnancy rate (RR = 0.77; 95% CI: 0.17 – 3.42) or live birth rate (RR = 0.99; 95% CI: 0.60 – 1.63). In a subgroup analysis, the intrauterine injection of > 500 IU hCG led to a significant increase in the implantation rate (RR = 1.64; 95% CI: 1.04 – 2.61) relative to controls. Furthermore, the subgroup of women with cleavage-stage ETs who received an intracavity injection of hCG (IC-hCG) exhibited increases in the implantation, clinical pregnancy and ongoing pregnancy rates, compared to women with cleavage-stage ETs and no IC-hCG. The current evidence indicates that intrauterine hCG administration before ET provides an advantage in terms of the clinical pregnancy and ongoing pregnancy rates.
Keywords: human chorionic gonadotropin; intrauterine injection; embryo transfer; meta-analysis